(untitled) (Research, Society and Development, 2021)
The Health Multiprofessional Residency Program (HMRP) is a postgraduate modality (Lato Sensu), whose offers a theoretical and practical training, in order to train specialists from different professional areas of health with the capacity to promote integrated actions and aiming at the prevention, promotion and rehabilitation of patients. This article seeks to report the perspectives and main challenges of a professional physiotherapist inserted in the Multiprofessional Residency Program in Comprehensive Care in Traumatology and Orthopedics linked to the University of the State of Pará (UEPA). This is a descriptive report of a retrospective experience, of the insertion and performance of a physiotherapist in the physiotherapy clinic of a Regional Hospital, with activities carried out from March to May 2021. The perspectives about the HMRP are that it trains a professional with an humanista and generalist training, as well as makes him capable to being responsible for acting in a critical and reflective way, with autonomy, responsibility, ethical conduct, as well as scientific and intellectual rigor in the area of traumatology and orthopedics. However, the challenges faced in these first months range from the lack of multidisciplinary work at the HRBA outpatient clinic to the extensive theoretical and practical workload, including the lack of specific discipline in the first year of residency. It is concluded that despite the burden caused to the resident due to the extensive workload of the program, the multidisciplinary residency in orthopedics and traumatology provides a practical theoretical experience that enriches the professional’s range of experience, effectively contributing to patient care.